2004
DOI: 10.2519/jospt.2004.34.6.305
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Training Improves Single-Limb Stability in Young Female Athletes

Abstract: Study Design: Controlled single-group pretest/posttest design. Objective: The purpose of this study was to determine if a 6-week neuromuscular training program designed to decrease the incidence of anterior cruciate ligament (ACL) injuries would improve single-limb postural stability in young female athletes. We hypothesized neuromuscular training would result in an improvement in postural stability, with the greatest improvement taking place in the medial-lateral direction. Background: Balance training has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
3
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 275 publications
(182 citation statements)
references
References 46 publications
10
162
3
7
Order By: Relevance
“…The YBT-LQ assesses ROM, strength, and neuromuscular control of the lower extremity and was chosen to assess the participants' lower limb balance. Numerous prior studies have demonstrated its utility as a clinical test to assess for lower limb balance deficits in the athletic population 10,[13][14][15] . Measurements were taken in three distinct directions of anterior (ANT), posteromedial (PM) and posterolateral (PL) on both the dominant and non-dominant limbs.…”
Section: Y-balance Testmentioning
confidence: 99%
See 2 more Smart Citations
“…The YBT-LQ assesses ROM, strength, and neuromuscular control of the lower extremity and was chosen to assess the participants' lower limb balance. Numerous prior studies have demonstrated its utility as a clinical test to assess for lower limb balance deficits in the athletic population 10,[13][14][15] . Measurements were taken in three distinct directions of anterior (ANT), posteromedial (PM) and posterolateral (PL) on both the dominant and non-dominant limbs.…”
Section: Y-balance Testmentioning
confidence: 99%
“…This test not only measures neuromuscular control but has also been correlated to quadriceps and hip strength. 9,10 Particularly the anterior reach portion demonstrates high activation of the vastus medialis and lateralis. 11 The YBT-LQ has not been studied preoperatively in an ACL-R population to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of neuromuscular imbalances and failure to have a neuromuscular spurt after the onset of puberty may be linked to the increased ACL injury risk in females relative to males [33,37,65,90]. Sex differences in landing mechanics, force absorption, muscle recruitment, and joint stability that occur during maturation can be modified with neuromuscular training programs [41,60,83]. Induction of a neuromuscular spurt in pubertal and postpubertal females may be important for ACL prevention strategies.…”
Section: Risk Factors and Mechanismsmentioning
confidence: 99%
“…We have evaluated common assessment tools such as the star excursion balance test, functional hop tests, stabilometry, and dynamometry, in addition to developing new techniques to help identify lower extremity asymmetry and high-risk landing and cutting techniques [13,44,69,72,78,83].…”
Section: Prediction and Assessment Of At Risk Individualsmentioning
confidence: 99%